Beyond Profit: Understanding The Foundations And Future Of Islamic Banking - Dr Ravi Sharma (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Islamic banking stands as a unique and dynamic facet within the global financial landscape, carving its niche based on the principles laid out by Sharia, the Islamic law. Rooted in ethical considerations and the prohibition of usury, Islamic banking offers a distinctive approach to financial services that aligns with the principles of fairness, transparency, and risk-sharing. As a rapidly growing sector, it attracts attention not only from Muslim-majority countries but also from diverse global markets seeking alternative financial paradigms